Washback Effects of English Reading Test in UTBK: Students’ Insights - Reffi Sabillawati; Fira Khasanah Ardiana (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Ujian Tulis Berbasis Komputer (UTBK) is a high-stakes test for students. They strive to pass the test and be accepted in their targeted institution. As one of the subjects involved in UTBK, the English test surely has influenced English teaching & learning in 12th-grade classrooms. This impact is known as the washback effect. While most studies investigate the washback effect on a test as a whole subject, little is known about the effect on the particular part of the test. Thus, this case study explores the washback effect of the English reading test in UTBK on the students’ perceptions, learning motivation, learning strategies, and learning content. The data were collected through online questionnaires distributed to six participants from different senior high schools. The deductive analysis found that the test has positive and negative effects seen from the students’ insights. UTBK can avoid cheating and integrate students’ English competence, but they are uncertain that it can improve their communicative competence. This study might enrich educational studies in English language teaching in general and language assessment in particular.